Tawur Kesanga As Harmonization And Existence Of Balinese Hindu “Diaspora” Culture In The City Of Palangka Raya - Ni Nyoman Rahmawati; Kahayanni Sinta (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2023)
Tawur Kesanga is a series of Nyepi days as a form of alignment, harmonizing the universe (Cosmos) from various disturbing negative influences. Tawur Kesanga is represented through the implementation of the ritual mecaru (bhuta kala) at the catus pate (crossroad). Then proceed with the ogoh-ogoh parade. Ogog-ogoh in the Tawur Kesanga ritual is the power of Bhuta Kala in the teachings of Hinduism. Besides that, ogoh-ogoh is also a work of art influenced by Balinese culture so that it becomes the identity of the Balinese people. Therefore the ogoh-ogoh parade in the series of Nyepi Day celebrations is not only a sacred religious ritual for Balinese Hindus but also a Balinese identity that is well known to foreign countries. The problem in this article is how the Tawur Kasanga Ritual can represent harmony and at the same time as the existence of Balinese diaspora culture in the City of Palangka Raya. This problem is analyzed using the theory of cultural accommodation, the informants are determined through Porposive sampling, the data is taken through observation, interviews, and documentation. Then it is analyzed through three stages, namely data collection, data reduction, and data presentation. The results in this article are (1) harmonization of the universe (cosmos) at the time of Tawur Kesanga is carried out through pecaruan ritual with the aim of giving food to bhuta kala so that later it will return to good (positive) characteristics. (2). Ogoh-ogoh as the cultural existence of the Balinese diaspora in Palangka Raya City can be seen from the enthusiasm of the local community in welcoming the ogoh-ogoh parade, the many Hindu organizations taking part in the ogoh-ogoh parade, the increasing number of types of ogoh-ogoh participating in the parade. Keywords: Ogoh-ogoh, Existence, Culture, Balinese Hindu Diaspora